PENGARUH JOB HUNGGING TERHADAP KERJA MILINEAL DAN GEN Z PADA PT. HAS INTERNASIONAL: PENGARUH JOB HUNGGING TERHADAP KERJA MILINEAL DAN GEN Z PADA PT. HAS INTERNASIONAL - Hendriawan Patadungan; Nur Fadhilah Safrillah; Fitriana Umar; Rima Yanti (LP2M IBK Nitro, 2026)
This study aims to analyze the effect of job hugging on the job performance of Millennial and Generation Z employees at PT. HAS International. Job hugging refers to a condition in which employees remain in their jobs primarily due to job security and fear of losing employment, despite declining motivation and engagement. This research employed a quantitative approach using a survey method. The sample consisted of 30 respondents selected through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression and t-test analysis. The results indicate that job hugging has a negative and significant effect on employee job performance. Higher levels of job hugging are associated with lower job performance. These findings highlight the importance of managerial efforts to create a supportive work environment that enhances employee engagement and career development, particularly for Millennial and Generation Z employees. Keywords: Job hugging, Job performance, Millennials, Generation Z.